Kolaborasi Sebagai Strategi Bisnis Masa Depan - Raharja, Sam’un Jaja (Jurnal Administrasi Bisnis, 2009)
Relations among organization have changed from independent to interdependent. Tomanage a relation between organization or corporation, suggest to implementationconcept of collaboration and coo-petition, as the condition of the world : changingrapidly, dynamics and interdependent.Keywords: Business strategy, collaboration and coo-petition